2016
DOI: 10.1002/ece3.2603
|View full text |Cite
|
Sign up to set email alerts
|

Good‐bye to tropical alpine plant giants under warmer climates? Loss of range and genetic diversity inLobelia rhynchopetalum

Abstract: The main aim of this paper is to address consequences of climate warming on loss of habitat and genetic diversity in the enigmatic tropical alpine giant rosette plants using the Ethiopian endemic Lobelia rhynchopetalum as a model. We modeled the habitat suitability of L. rhynchopetalum and assessed how its range is affected under two climate models and four emission scenarios. We used three statistical algorithms calibrated to represent two different complexity levels of the response. We analyzed genetic diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
57
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 96 publications
(66 citation statements)
references
References 44 publications
7
57
0
2
Order By: Relevance
“…Chala et al, 2016;Gregr et al, 2018) and As expected, we found parameterizations of intermediate complexity to yield highest TSS and AUC.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Chala et al, 2016;Gregr et al, 2018) and As expected, we found parameterizations of intermediate complexity to yield highest TSS and AUC.…”
Section: Discussionsupporting
confidence: 84%
“…transferability) of models fitted from comparably complex parameterizations (e.g. Chala et al, 2016;Gregr et al, 2018) and of comparably complex SDM algorithms (e.g. Randin et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Spatially restricted cryophilic species (e.g. Espeletiopsis colombiana , Coespeletia timotensis and Pycnophyllum tetrastichum ) would be particularly prone to a loss of climate niche space (Mavárez, Bézy, Goeury, Fernández, & Aubert, ), in agreement to the expected range contraction and loss in genetic diversity of Afrotropical alpine species suggested by model projections (Chala et al, ). Additional pressures on thermal narrow‐range specialists could arise from increases in seasonal temperature variability (IPCC, ), coupled with decreases in diurnal temperature variability due to faster night‐time versus daytime warming (Easterling et al, ).…”
Section: Discussionsupporting
confidence: 76%
“…The few grid cells that were not deemed suitable for stem succulents by the models but did contain at least two observed genera were manually assigned as presence. For the assignment of species to the succulent biome (see below), the continuous stem succulents map was converted to binary with a threshold of 33% (partially following Chala et al, 2016).…”
Section: Methodsmentioning
confidence: 99%